The Effect of Leadership, Workload and Work Stress on Employee Performance: The Case of General Election Commision Voting Committee Secretariat at Ogan Ilir District for the Election of Regional Head and Vice Regional Head in 2024) - Ningsih, Feby Ayu; Idris, Muhammad; Tobari, Tobari (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine 1) The Influence of Leadership, Workload, and Work Stress on the Performance of Employees of the Secretariat of the Voting Committee of the General Election Commission of Ogan Ilir Regency (Regional Head and Deputy Regional Head Elections in 2024). 2) The Influence of Leadership on the Performance of Employees of the Secretariat of the Voting Committee of the General Election Commission of Ogan Ilir Regency (Regional Head and Deputy Regional Head Elections in 2024). 3) The Influence of Workload on the Performance of Employees of the Secretariat of the Voting Committee of the General Election Commission of Ogan Ilir Regency (Regional Head and Deputy Regional Head Elections in 2024). 4) The Influence of Work Stress on the Performance of Employees of the Secretariat of the Voting Committee of the General Election Commission of Ogan Ilir Regency (Regional Head and Deputy Regional Head Elections in 2024). This type of research is Associative. The variables used by the researcher are leadership variables, workload, work stress, and employee performance. The sample in this study was 257 employees of the Secretariat of the Election Committee of the Ogan Ilir Regency General Election Commission (Regional Head and Deputy Regional Head Elections in 2024) who were selected using Cluster Random Sampling. The data used in this study were primary data collected using a questionnaire. The data analysis technique used was multiple linear regression. The results of this study indicate that (1) leadership, workload, and work stress together have a positive and significant effect on employee performance, and (2) leadership has a positive and significant effect on employee performance. (3) workload has a positive and significant effect on employee performance. (4) work stress has a positive and significant effect on employee performance